Unraveling High‐Yield Phase‐Transition Dynamics in Transition Metal Dichalcogenides on Metallic Substrates - Yin, Xinmao (Adv Sci (Weinh), 2019)
2D transition metal dichalcogenides (2D‐TMDs) and their unique polymorphic features such as the semiconducting 1H and quasi‐metallic 1T′ phases exhibit intriguing optical and electronic properties, which can be used in novel electronic and photonic device applications. With the favorable quasi‐metallic nature of 1T′‐phase 2D‐TMDs, the 1H‐to‐1T′ phase engineering processes are an immensely vital discipline exploited for novel device applications. Here, a high‐yield 1H‐to‐1T′ phase transition of monolayer‐MoS(2) on Cu and monolayer‐WSe(2) on Au via an annealing‐based process is reported. A comprehensive experimental and first‐principles study is performed to unravel the underlying mechanism and derive the general trends for the high‐yield phase transition process of 2D‐TMDs on metallic substrates. While each 2D‐TMD possesses different intrinsic 1H‐1T′ energy barriers, the option of metallic substrates with higher chemical reactivity plays a significantly pivotal role in enhancing the 1H‐1T′ phase transition yield. The yield increase is achieved via the enhancement of the interfacial hybridizations by the means of increased interfacial binding energy, larger charge transfer, shorter interfacial spacing, and weaker bond strength. Fundamentally, this study opens up the field of 2D‐TMD/metal‐like systems to further scientific investigation and research, thereby creating new possibilities for 2D‐TMDs‐based device applications.